2022
DOI: 10.33545/surgery.2022.v6.i3b.921
|View full text |Cite
|
Sign up to set email alerts
|

Wang procedure: A reasonable choice for reoperation after failure of Nuss procedure for pectus excavatum

Abstract: Pectus excavatum is a common thoracic deformity, and Nuss procedure is considered as the standard operation for the treatment of this deformity. However, there are often cases of Nuss procedure failure in the clinic. Once such a situation occurs, it often needs to be operated again. Since Nuss procedure can cause adhesions behind the sternum and in the bilateral thoracic cavities, if Nuss procedure is still used in the reoperation, it is not only very difficult, but also possible to cause heart and lung injuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 8 publications
0
27
0
1
Order By: Relevance
“…The operation was completed under general anesthesia. The main operation includes two procedures, namely Wenlin procedure [17][18][19][20][21] and Wang procedure [22][23][24][25] . The supine position was adopted, and a median incision was made.…”
Section: ~ 69 ~mentioning
confidence: 99%
“…The operation was completed under general anesthesia. The main operation includes two procedures, namely Wenlin procedure [17][18][19][20][21] and Wang procedure [22][23][24][25] . The supine position was adopted, and a median incision was made.…”
Section: ~ 69 ~mentioning
confidence: 99%
“…Since Nuss procedure appeared, the treatment of thoracic deformity has entered the era of minimally invasive surgery [4] . All the operations for the treatment of thoracic deformity are divided into two categories: one is for depression deformity, including Nuss procedure [4] , Wang procedure [5][6][7][8][9] and Wung procedure [10,11] ; the other is for protrusion deformity, including Abramson procedure [12] and Wenlin procedure [13][14][15][16][17][18] . From the nature of surgery, Nuss procedure [4] and Abramson procedure [12] are mechanical external force plastic surgery, while Wang procedure and Wenlin procedure are template plastic surgery [1,2] .…”
Section: ~ 26 ~mentioning
confidence: 99%
“…Wang procedure [5][6][7][8][9] and Wenlin procedure [13][14][15][16][17][18] are direct plastic surgery, mainly aiming at local correction of lesions, which are more suitable for the treatment of acute angle deformity theoretically. However, as mentioned above, acute angle deformity is a very severe structural change, and there is often severe bone hyperplasia at the top of the acute angle.…”
Section: ~ 26 ~mentioning
confidence: 99%
“…Children at this age are not suitable for Nuss procedure, which can be an important supplement to Nuss procedure. In the later application process, it was found that Wang procedure was especially suitable for pectus excavatum surgery on some special occasions: (1) Reoperation after pectus excavatum surgery failed [14] . After the first operation, these patients usually have severe adhesion behind the sternum.…”
Section: Introductionmentioning
confidence: 99%